2009
DOI: 10.1016/j.ica.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative discrimination of fake and true alkene rotation processes in pd(η2-olefin) complexes. A new bimolecular mechanism

Abstract: H NMR spectroscopy and quantitatively determined by line-shape analyses (for 2) and selective inversion recovery experiments (for 3). The coalescence of the AB multiplet of fn hydrogens of 2 is concentration dependent and presents a strongly negative DS -, suggesting the intermediacy of a dimeric complex and ruling out the hypothesis of olefin rotation. The accurate evaluation of all spectral features also allows determination of the approaching mode of the monomeric units. The inversion transfer between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…noticed that the apparent olefin rotation can also originate from the collapse of a dimeric species produced by action of the lone pair on sulfur which attacks another palladium centre via a bimolecular mechanism [51,52]. In these cases it has been demonstrated that the authentic olefin propeller-like rotation occurs at a negligible rate with respect to that observed when the associative mechanism is operative.…”
Section: Fluxional Rearrangementsmentioning
confidence: 99%
“…noticed that the apparent olefin rotation can also originate from the collapse of a dimeric species produced by action of the lone pair on sulfur which attacks another palladium centre via a bimolecular mechanism [51,52]. In these cases it has been demonstrated that the authentic olefin propeller-like rotation occurs at a negligible rate with respect to that observed when the associative mechanism is operative.…”
Section: Fluxional Rearrangementsmentioning
confidence: 99%
“…Using experimental evidence and reasons of symmetry, Canovese et al showed that a mechanism including intermediate S9 could not be correct. Only the collapse of the intermediate S6 allows the exchange between the ligand coordinating atoms and the consequent olefin pseudo rotation independently of the olefin enantioface (Scheme 5) [10,11]. Our calculations showed as well that S7 ( Figure 5) is more stable than S9 ( Figure 6) Figure 6 shows the optimised structure of TSS6S7.…”
Section: Results and Disscussionmentioning
confidence: 61%
“…The fluxional processes of palladium(0) complexes of type [Pd(η 2 -olefin)(L-L´)] and their mechanisms have been studied in detail experimentally [10,11]. The mechanisms put forward for the fluxional movements in olefin complexes of Pd are listed below [3,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations